A hybrid approach to exchange rates: How do macro news and order flow affect exchange rate volatility?. Issue 1 (7th March 2016) - Zhang, Guangfeng; Marsh, Ian; MacDonald, Ronald
Abstract : Purpose: – This study aims to investigate the impact of information, both public macro news and private information, on exchange rate volatility in an integrated framework. Design/methodology/approach: – The authors apply real-time data of macro announcements and high-frequency trading data (German Deutsche Mark to US dollar, DEM/USD, from 1 May to 31August 1996) to GARCH models and examine various model specifications. Findings: – Data analysis demonstrates real-time macro news and market makers' private information both have a significant impact on exchange rate volatility, but there is no interaction between macro and micro information in the information transmission process. Originality/value: – This study contributes to empirical hybrid studies of examining exchange rates volatility, which is in line with literature that combine both macro and micro fundamentals in examining exchange rates variation. Particularly, a key element of this study is to use a microstructure fundamental variable, namely, order flow, to capture private information in an exchange rate volatility study.